A study of nonlinear pedagogical teaching models for cognitive and affective development of elementary school students - Yuliarto, Hari (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2024)
This research aims to advance the psychomotor, cognitive, and affective abilities of elementary school students through a nonlinear pedagogical approach. The method adopted is research and development which combines quantitative and qualitative analysis. From a total of 2,411 elementary school teachers in 150 elementary schools spread across the Kota District area, 52 teachers were selected as the sample in this study. Data analysis uses a quantitative descriptive approach, with a focus on the use of percentages. The results show teachers' understanding of nonlinear pedagogy with a general average score of 2.705, indicating relatively good performance. However, the lowest rating was found in the item